Association of deprivation with overweight and obesity among primary school children in England: an ecological cross-sectional study. (November 2017) - Little, Emma; Nestel, Penelope
Abstract: Background: In England, levels of childhood overweight–obesity have increased for numerous reasons, including deprivation that is often measured with the English Index of Multiple Deprivation (IMD). The IMD comprises seven domains (income; employment; education, skills, and training; health deprivation and disability; crime; barriers to housing and services; and living environment). Whether individual IMD domains are associated with childhood overweight–obesity remains unknown. The aim of this study was to investigate the association between individual IMD domains and overweight–obesity among primary schoolchildren and whether this varied among overweight, obesity, children in Reception, children in Year 6, and region. Methods: Secondary subgroup analyses at a local authority level (n=324) were conducted with data obtained from the National Child Measurement Programme 2011–12 to 2014–15, IMD 2015 domains including a supplementary index (Income Deprivation Affecting Children Index [IDACI]), and 2011 Census data. Univariate analysis was used to investigate the association of IMD domains with overweight–obesity, with predictors (p<0·05) incorporated into multiple linear regression models. Findings: After adjustment for significant (p<0·05) confounders, mainly region and ethnicity, all IMD domains were associated with overweight–obesity (p<0·0001), and a positive linear association was observed in both Reception and Year 6, apart from barriers to housing and services for all age and weight categories and crime in overweight children in Reception. This was more evident for obese than overweight children, and children in Year 6 than in Reception. Overall IMD and IDACI showed the strongest overall associations with childhood overweight–obesity, but health, education, and employment showed the strongest associations for certain age and weight categories, and a regional variation was seen. Interpretation: Overweight–obesity is multifactorial, and a national holistic approach to control childhood overweight–obesity is required. Although overall IMD and IDACI scores were most strongly associated with childhood overweight–obesity and should still be used as a measure of deprivation, other IMD domains can also be considered in public health interventions for childhood overweight–obesity to enable effective identification of all at-risk populations. Funding: None.